Digital marketing of commercial infant formula in Argentina: a digital ethnographic study - Flavia Demonte; Daniela Paola Bruno; María Celeste Nessier; María Elisa Zapata (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2024)
Although evidence of the benefits of breastfeeding is widespread, there are several challenges to initiate and sustain it. Infant formula companies use marketing strategies that violate existing regulations, contributing to its early abandonment. We explore the digital marketing exposure of infant formulas in Argentina by analyzing people's interactions with brands and the traces of these interactions in conversations engaged in Facebook groups during 2022, from a qualitative approach based on digital ethnography. Results show that companies deploy regulatory avoidance tactics and seek contact with mothers. Users do not interact with the accounts but are exposed to their strategies given the correlation between product attributes present in advertising with their motivations and aspirations. The mediators between marketing and mothers are medical professionals, used as marketing resources. We conclude that authorities should promote new agreements on the practices of medical professionals and develop regulations taking into account digital environments.